Hybrid structure combining essential oil derivatives and polydopamine for anti-bacterial coatings - Jourdainne, Nathan; Mercier, Dimitri; Costa, Bruna; Campos, Filipa; Monteiro, Claudia; Costa, Natália [UNESP]; Martins, M. Cristina L.; Thébault, Pascal (My University, 2025)
The development of effective antimicrobial surfaces is crucial for reducing the risk of medical device-associated infections. This study investigates the antibacterial potential of carvacrol (CAR), a natural essential oil, after their surface immobilization onto gold (Au) substrates through a polydopamine (pDA) layer. The successful deposition and properties of each layer were characterized using ellipsometry, water contact angle (WCA) measurements, Fourier Transform Infrared Reflection-Absorption Spectroscopy (FT-IRRAS), X-ray Photoelectron Spectroscopy (XPS), and Atomic Force Microscopy (AFM). The resulting coatings displayed a thin, uniform film with smooth topography and with enhanced hydrophilicity. Antibacterial efficacy was assessed against Staphylococcus epidermidis, a relevant etiological agent in this context. The results revealed that the polydopamine-carvacrol coated surfaces (Au-pDA-CAR) exhibited a significant reduction in bacterial viability, achieving a 96 % decrease compared to unmodified gold surfaces. This was contrasted with minimal antibacterial activity from surfaces with either only polydopamine (Au-pDA) or carvacrol (Au-CAR). Live/Dead bacterial viability assays confirmed the bactericidal effect of the Au-pDA-CAR surface, demonstrating its effectiveness in killing bacteria rather than merely preventing adhesion. Our findings indicate that the pDA-CAR coating presents a promising approach for developing antimicrobial surfaces with enhanced performance against biofilm-forming pathogens. The development of this coating is an important step towards the establishment of a new technological platform capable of preventing medical device associated infections.
Keywords: Antibacterial surfaces; Carvacrol; Essential oil; Medical device associated-infections; Polydopamine; Surface characterization; Surface modification